Afghanistan : the essential guide to customs & culture - Najib, Moska; Afroz, Nazes (London : Kuperard, 2013)
Guide to Afghan culture and society, to turn your visit into a memorable an denriching experience.
Land and people -- Values and attitudes -- Customs and traditions -- Making friends -- Private and family life -- Time out -- Travel, health, and safety -- Business briefing -- Communication.
Includes bibliographical references (page 165) and index.
Keywords: Afghanistan -- Guidebooks; Afghanistan -- Social life and customs